2017
DOI: 10.1002/nau.23345
|View full text |Cite
|
Sign up to set email alerts
|

The association of lower urinary tract symptoms with incidental falls and fear of falling in later life: The Community Health Survey

Abstract: This study emphasizes the relationship between LUTS and falling. Furthermore, increased LUTS severity led to a higher risk of incidental falls. A high correlation between fear of falling and LUTS was also observed in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
(86 reference statements)
2
15
0
Order By: Relevance
“…Incontinence was a risk factor for falls in both urban (OR = 8.792) and rural areas (OR = 11.396). This is consistent with the results from Choi and Kim's studies [17,19] , indicating that incontinence is a common risk factor across different regions and populations. Incontinence causes a corresponding increase in the frequency of urination in older adults, which itself is increased further due to an increased water intake resulting from the hot climate in Shantou and the rich tea culture in China.…”
Section: Similar Risk Factors For Both Areassupporting
confidence: 92%
“…Incontinence was a risk factor for falls in both urban (OR = 8.792) and rural areas (OR = 11.396). This is consistent with the results from Choi and Kim's studies [17,19] , indicating that incontinence is a common risk factor across different regions and populations. Incontinence causes a corresponding increase in the frequency of urination in older adults, which itself is increased further due to an increased water intake resulting from the hot climate in Shantou and the rich tea culture in China.…”
Section: Similar Risk Factors For Both Areassupporting
confidence: 92%
“…Except Parsons et al's 6 and Noguchi et al's 23 studies, most previous studies reported that only urinary incontinence and overactive bladder symptoms (frequency, urgency, and nocturia) increased the risk of falls in the elderly men. 4,5,[7][8][9][10][11][12]24 Parsons et al 6 and Noguchi et al 23 reported that voiding symptoms such straining and incomplete emptying is also associated with falls in the elderly men. Based on these studies and ours, the possibility can be suggested that other LUTSs aside from the symptoms of overactive bladder can independently increase the risk of fall in men.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Attention on lower urinary tract symptoms (LUTSs) such as weak urine stream, hesitancy, and urgency has been increasing. [4][5][6][7][8][9][10][11][12] LUTSs are related to the storing and excretion of urine and include hesitancy, incomplete emptying, frequency, intermittency, urgency, nocturia, and weak urine stream. Benign prostatic hyperplasia and overactive bladder are known as the major causes of LUTSs in men.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations